Aumento da penetraç\~ao do serviço de acesso à Internet em banda larga e seu possível impacto econômico: Análise através de sistema de equaç\~oes simultâneas de oferta e demanda - Hildebrando Rodrigues Macedo; Alexandre Xavier Ywata de Carvalho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2010)
– Using demand and supply simultaneous equations, including endogenous variables, it was analyzed the possible economic impact on the GDP and GDP per capita, resulted of the increase in the broadband internet access diffusion in Brazil. Broadband penetration, GDP, GDP per capita and population education data were disaggregated at State level. Data about investment on broadband networks were nationally consolidated. Estimations, of the broadband accesses density per State, between 2000 and 2006, from the national densities, were required because lack of data detailed at State level. Only from 2007 on this data was available at the State (and municipality) level. The prices had also to be estimated due the lack of reliable data.
Keywords: C21; O33; 330; Internet; Nationaleinkommen; Bildungsniveau; Brasilien